Experimental performance evaluation and model-based optimal design of a mechanical vapour recompression system for radioactive wastewater treatment. (15th January 2022) - Hou, Chao; Lin, Wenye; Yang, Luwei; Zhang, Huafu
Highlights: Mechanical vapour recompression radioactive wastewater treatment system was studied. A model platform for the proposed system was developed and validated. Bi-objective design optimisation on payback period and efficiency was implemented. A Pareto front was achieved to facilitate the optimal system design. Abstract: High-security and cost-effective disposal of radioactive wastewater plays a significant role in the wide deployment of nuclear energy. This paper presents an experimental study to investigate the feasibility of using mechanical vapour recompression systems for radioactive wastewater treatment, and a model-based design optimisation to maximise its economic benefits. A lab-scale mechanical vapour recompression system was established to experimentally assess its performance in terms of decontamination effect, energy efficiency, and exergy destruction. Based on the understanding of system performance, a numerical model for the proposed mechanical vapour recompression system was developed and validated, which was then utilised as a platform for optimal system design. A bi-objective design optimisation was formulated with the targets to minimise the payback period of the additional cost referencing to a traditional three-effect-evaporation system while maximising the system primary energy efficiency. Two intermediate variables, including the evaporation temperature and the heat transfer temperature difference, were selected as the optimisation variables. The experimental results verified the feasibility of using mechanical vapour recompression technology for radioactive wastewater treatment, demonstrating an excellent decontamination capability. It was found that an optimal evaporation temperature of 90 °C existed for maximising the decontamination factors for ions of strontium, cobalt, and cesium to 5.90 × 10 3, 1.45 × 10 4, and 1.74 × 10 4, respectively, while a higher system efficiency (coefficient of performance ranging from 7.33 to 8.21) has resulted when increasing the evaporation temperature (from 70 to 100 °C, correspondingly). The design optimisation resulted in an optimal Pareto front presenting the trade-off between the two optimisation objectives. By adopting the design corresponding to the optimal solutions identified, the mechanical vapour recompression system was found to feature a relative payback period of 0.69–2.32 years and a primary energy efficiency of 3.94–13.46, which outperformed a comparison case without optimisation (with that of 2.79 years and 3.03, respectively). The outcomes of study will provide guidance for the optimal application of mechanical vapour recompression evaporation system in nuclear wastewater treatment.